1991
DOI: 10.1113/jphysiol.1991.sp018394
|View full text |Cite
|
Sign up to set email alerts
|

Chloride secretion stimulated by prostaglandin E1 and by forskolin in a canine renal epithelial cell line.

Abstract: SUMMARY1. The actions of prostaglandins upon ion transport in a renal-derived cultured epithelium (MDCK) have been investigated.2. Prostaglandin E1 (PGE1) stimulates an inwards short-circuit current (SCC) in voltage-clamped epithelial layers mounted in Ussing chambers. Measurements of transepithelial Cl-fluxes, cation and anion replacement of the bathing media and the use of the Cl-channel blocker 3-nitro-2(3-phenylpropylamino)-benzoic acid (NPPB) are consistent with the PGEl-stimulated inward SCC resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…The biphasic time course of the I sc response to cAMP (Fig. 2) was consistent with previous studies in MDCK cells (43,54) and in A6 cells (4,8,29,44,58) that showed a rapid increase in anion secretion followed by a more gradual increase in Na ϩ absorption. The secretory anion current, represented by NS-I sc , was partially inhibited by 200 M glibenclamide (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…The biphasic time course of the I sc response to cAMP (Fig. 2) was consistent with previous studies in MDCK cells (43,54) and in A6 cells (4,8,29,44,58) that showed a rapid increase in anion secretion followed by a more gradual increase in Na ϩ absorption. The secretory anion current, represented by NS-I sc , was partially inhibited by 200 M glibenclamide (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…Actually, prostaglandins are able per se to stimulate transepithelial ion transport in MDCK cells (Simmons, 1991). A mechanism through which prostaglandins can be generated is the Ca2+-dependent activation of phospholipase A2.…”
Section: Discussionmentioning
confidence: 99%
“…C Mean±SEM (n=5 pairs) for the effect of 0.1 mM furosemide on the initial rate of acidification of the cell cytosol following basal exposure to 5 mM NH 4 Cl tion of 10 -5 M forskolin stimulated inward I sc by 5.2±0.8 µA cm -2 (n=12) which is due to transepithelial anion secretion [3] Application of 0.2 mM furosemide during the maintained phase to the basal solutions resulted in only small reductions of the secretory current to 4.6±0.8 µA cm -2 (n=12) after 5 min incubation (83.5±5.3%, n=12, of the maintained response is insensitive to furosemide). Thus, in contrast to other secretory epithelia such as intestinal or MDCK epithelia [8,26,27,28,31], NKCC1 is not the major determinant of cAMP-stimulated anion secretion at the basolateral membrane of mIMCD-K2 cells.…”
Section: Transepithelial Anion Secretionmentioning
confidence: 98%